Limited resources restrict the provision of adequate neonatal respiratory care in the countries of Africa. (4th August 2021) - Tooke, Lloyd; Ehret, Danielle E. Y.; Okolo, Angela; Dlamini‐Nqeketo, Sithembile; Joolay, Yaseen; Minto'o, Steeve; Pillay, Shakti; Abdallah, Yaser; Naburi, Helga; Ndour, Daouda; Brobby, Naana; Stevenson, Alexander G.
Abstract: Aim: Over two thirds of newborn deaths occur in Africa and South Asia, and respiratory failure is a major contributor of these deaths. The exact availability of continuous positive airway pressure (CPAP) and surfactant in Africa is unknown. The aim of this study was to describe the availability of newborn respiratory care treatments in the countries of Africa. Methods: Surveys, in English, French and Portuguese, were sent to neonatal leaders in all 48 continental countries and the two islands with populations over 1 million. Results: Forty‐nine (98%) countries responded. Twenty‐one countries reported less than 50 paediatricians, and 12 countries had no neonatologists. Speciality neonatal nursing was recognised in 57% of countries. Most units were able to provide supplemental oxygen. CPAP was available in 63% and 67% of the most well‐equipped government and private hospitals. Surfactant was available in 33% and 39% of the most well‐equipped public and private hospitals, respectively. Availability of CPAP and surfactant was greatly reduced in smaller cities. Continuous oxygen saturation monitoring was only available in 33% of countries. Conclusion: The availability of proven life‐saving interventions in Africa is inadequate. There is a need to sustainably improve availability and use of these interventions.